PENGARUH DOSIS HERBISIDA GLIFOSAT TERHADAP BEBERAPA JENIS GULMA UTAMA PERKEBUNAN KELAPA SAWIT - Hangger Gahara Mawandha; A.T Soejono; Fiona Alfani (AGROISTA : Jurnal Agroteknologi, 2018)
This research aims to know the dosage of herbicide glyphosate is effective and efficient against the sensitivity of Imperata cylindrica, Chromolaena odorata, Cyperus rotundus. This research was carried out on the fields of education and research (KP2) Institute for agriculture Stiper Yogyakarta which is located in the Subdistrict of Depok, Maguwoharjo, Sleman Regency, Yogyakarta special region province. Implemented in December 2016 until January 2017. This study used a factorial experiment method which consisted of two factors, which are arranged in a randomized complete design (RAL), the first factor is a type of weed that consists of three types, namely, Imperata cylindrica, Chromolaena odorata, Cyperus rotundus. The second factor is the level of dose consisted of 3 levels namely controls, 5 l/ha, and 6 l/ha. The data were analyzed using a analysis of varience and to know the difference between the treatment performed testing using the DMRT (Duncan Multiple Range Test) on the real level of 5%. The results of the analysis of the three kinds of weed applied herbicide doses 5 l/ha and 6 l/ha glyphosate treatment, dosage 6 l/ha is efficient in controlling Cyperus rotundus, while treatment of glyphosate doses of 6 l/ha control Imperata cylindrica and effective Chromolaena odorata. Cyperus rotundus is the weed with a high level of sensitivity towards the treatment of herbicide dose 5 l/ha and 6 l/ha. Keywords : Imperata cylindrica, Chromolaena odorata, Cyperus rotundus, dose levels of the herbicide glyphosate